1990
DOI: 10.1254/jjp.54.93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serotonin on Blood Glucose and Insulin Levels of Glucose- and Streptozotocin-Treated Mice

Abstract: Abstract-Effectsof serotonin (5-HT) on plasma glucose and serum insulin levels were studied in mice. In normal mice, 5-HT induced a dose-dependent hypo glycemia and an increase in serum insulin levels. 5-HT significantly inhibited glucose-induced hyperglycemia and increased glucose-stimulated insulin release. However, in streptozotocin-induced diabetic mice, 5-HT changed neitheir the glucose nor insulin levels. These results strongly suggest that 5-HT-induced hypoglycemia is brought on by increasing serum insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Several lines of evidence suggest a role for serotonin in the regulation of energy balance, specifically in relation to glucose and fatty acid metabolism. Serotonin is known to induce hepatic regeneration (Lesurtel et al 2006), glucose secretion from the liver, and insulin secretion by the pancreas (Sugimoto et al 1990, Watanabe et al 2011 as well as liver glucose uptake mechanisms (Moore et al 2004(Moore et al , 2005 and glycogen metabolism (Papadimas et al 2012). Furthermore, serotonin has been shown to regulate glucose-stimulated insulin secretion by the b cells of the pancreas during pregnancy, and it is critical for glucosestimulated insulin secretion in an insulin-resistant state (Ohara-Imaizumi et al 2013, Kim et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence suggest a role for serotonin in the regulation of energy balance, specifically in relation to glucose and fatty acid metabolism. Serotonin is known to induce hepatic regeneration (Lesurtel et al 2006), glucose secretion from the liver, and insulin secretion by the pancreas (Sugimoto et al 1990, Watanabe et al 2011 as well as liver glucose uptake mechanisms (Moore et al 2004(Moore et al , 2005 and glycogen metabolism (Papadimas et al 2012). Furthermore, serotonin has been shown to regulate glucose-stimulated insulin secretion by the b cells of the pancreas during pregnancy, and it is critical for glucosestimulated insulin secretion in an insulin-resistant state (Ohara-Imaizumi et al 2013, Kim et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The liver expresses TPH1 and several serotonin receptor subtypes (Papadimas et al 2012). Serotonin is thought to mediate hepatic regeneration (Lesurtel et al 2006) as well as glucose and insulin secretion (Sugimoto et al 1990). Studies have shown that serotonin is involved in liver glucose uptake mechanisms (Moore et al 2005) and glycogen metabolism (Papadimas et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of insulin-dependent hypoglycemic effect of serotonin (Yamada et al, 1989;Sugimoto et al, 1990), SSRIs, or monoamine oxidase inhibitors (Lundquist et al, 1971;Furman, 1974;Smith and Pogson, 1977;Wilson and Furman, 1982;Gomez et al, 2001;Pollak et al, 2001) has been provided in many previous studies. Not all of the SSRIs lowered the plasma glucose in association with the increase of plasma insulin level (Erenmemisoglu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Weaver et al (2016) and Hernández-Castellano et al (2017) demonstrated that the infusion of the 5-HT precursor 5-hydroxytryptophan (5-HTP) during the last days before parturition improved blood calcium concentrations around parturition. Additionally, 5-HT has been shown to influence several metabolites related to glucose and lipid metabolism such as glucose, insulin, triglyceride, cholesterol, and fatty acid concentrations in mice (Sugimoto et al, 1990;Watanabe et al, 2010) and sheep (Watanabe et al, 2014). Moreover, 5-HT promotes the proliferation and activation of B cells in mice (Iken et al, 1995), and therefore the IgG concentration could also be affected by the increased 5-HT concentration in blood.…”
Section: Introductionmentioning
confidence: 99%